Coffee Producers rethinking their participation in the coffee chain: Cases of Mexico and Costa Rica - Luna González, Alejandro (2018)
The main market for coffee producers’ countries are abroad, particularly when such markets are under the control of few international companies who buy de product. This lead some countries like Mexico and Costa Rica to develop changes in the way they participate in value chain, where the quality of the coffee is decisive at the moment of negotiating a better price for the producer. The main objective of this research was to compare the value-added strategies in both countries, based on certification’s adoption and a quality management processes. We did use the global value chain approach to analyze the producer’s strategy who transform or process the coffee ll in “Beneficiaries” or mills). The information was obtained from 64 Coffee mills, 67.1%in Costa Rica and 32.9% in Mexico. We found that in the case of Costa Rica there is a Pearson correlation of .457 (significant at P <.05), between having certifications and installed capacity. In Mexico´s case, the Pearson correlation was of .693 (significant at P <.05), between having certifications and obtaining better income. The coffee certification is a very commonly used strategy, to access to sales channels by volume in Costa Rica, while in Mexico a price strategy is more frequent. The coffee selection in the mill is a main issue to increasethe quality of the coffee, allowing innovation in different specialized products and commercializing them in both traditional markets and new markets. The adoption of a quality management strategy would enable the integration in the coffee chain.